“I Wanted to Feel Like a Man Again”: Hegemonic Masculinity in Relation to the Purchase of Street-Level Sex - Shumka, Leah; Strega, Susan; Hallgrimsdottir, Helga Kristin (Frontiers in Sociology, 2017)
This paper examines the narratives of men who purchase sex from street level providers in a mid-sized city in Western Canada. We explore what men’s stories tell us about how masculinity is constructed in relation to street sex work. These men narrated their purchase of sex as attempts to exercise or lay claim to male power, privilege, and authority; at the same time, research reveals how tenuous this arrangement is for men. Study participants drew on conventional heterosexual masculine scripts to rationalize their actions and behaviors. Their stories reveal that their purchase of street-level sex is motivated by a sense of failure to successfully align with classed and gendered norms of hegemonic masculinity in which the purchase of sex was an attempt to “feel like a man again”. In this paper we move beyond the notion that static “types” of men purchase sex, highlighting instead that sex work customers are complex social actors with multifaceted reasons for purchasing sex but that are nonetheless inseparable from socially valorized forms of masculine comportment. We conclude that hegemonic masculinity is not only injurious to some men, but also to the sex workers on whom it is enacted.